2019
DOI: 10.1097/wad.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Risk Factors for Alzheimer Disease Among Community-Dwelling, Nondemented Older African Americans

Abstract: Purpose: Heightened Alzheimer disease (AD) risk among African Americans represents a racial disparity in aging. This study examines perceptions of AD risk factors among nondemented older African Americans. Methods: Participants indicated how important nine factors were in increasing one’s AD risk using a Likert-type scale with endpoints 1=not at all important to 4=extremely important. We examined perceptions of AD risk factors as a function of age, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…23 Though we did not observe similar differences here, this could be due to differential views specifically toward AD in these groups, such as attributing "God's will" as a risk factor. 24 Our findings may also differ from those in previous studies due to the focus on short-term distress or selection bias, including a willingness to participate in the A4 Study, likely favorable attitudes toward research, and higher education than the general population. 17 Earlier studies have reported that baseline levels of anxiety and depression may be predictors of distress after amyloid disclosure.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…23 Though we did not observe similar differences here, this could be due to differential views specifically toward AD in these groups, such as attributing "God's will" as a risk factor. 24 Our findings may also differ from those in previous studies due to the focus on short-term distress or selection bias, including a willingness to participate in the A4 Study, likely favorable attitudes toward research, and higher education than the general population. 17 Earlier studies have reported that baseline levels of anxiety and depression may be predictors of distress after amyloid disclosure.…”
Section: Discussioncontrasting
confidence: 97%
“…Hispanic participants reported greater distress compared to other racial and ethnic groups among stroke survivors 23 . Though we did not observe similar differences here, this could be due to differential views specifically toward AD in these groups, such as attributing “God's will” as a risk factor 24 . Our findings may also differ from those in previous studies due to the focus on short‐term distress or selection bias, including a willingness to participate in the A4 Study, likely favorable attitudes toward research, and higher education than the general population 17 …”
Section: Discussioncontrasting
confidence: 90%
“…Black patients are twice as likely not to seek out healthcare when experiencing thinking or memory problems than White patients ( Alzheimer’s Association, 2021 ). The reasoning behind the avoidance of healthcare intervention may be partly due to a lack of community educational outreach, as Black Americans are more likely to attribute ADRD symptoms to normal aging than White Americans ( Glover et al, 2019 ). As cultural education among physicians remains subpar, these nuances in recognizing symptoms and treating different populations of patients impair the quality of care for ADRD ( Assistant Secretary For Planning and Evaluation (ASPE), 2022 ).…”
Section: Outreach and Intervention Programs For Black Women With Adrdmentioning
confidence: 99%
“…The educational sessions were offered in the metropolitan area of Atlanta, Georgia and the results are not generalizable to the greater population. Research has shown an increased awareness of ADRD risk factors are significant to motivating behavior change in African-American adults (Glover, CoCroft, James, & Barnes, 2019…”
Section: Limitations and Recommendationsmentioning
confidence: 99%